2019
DOI: 10.1016/j.jjcc.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Association of potent P2Y12 blockers with ischemic and bleeding outcomes in non-ST-segment elevation myocardial infarction

Abstract: A B S T R A C TBackground: Potent P2Y12 blockers are preferred in patients with acute non-ST-segment elevation myocardial infarction (NSTEMI) undergoing percutaneous coronary intervention (PCI). However, the risk of bleeding remains a major concern. We assessed the association of potent P2Y12 blockers with ischemic and bleeding outcomes in patients with NSTEMI. Methods: From the Korea Acute Myocardial Infarction Registry-National Institute of Health database, 4927 patients with NSTEMI receiving drug-eluting st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…No significant differences were observed in the incidence of major bleeding between the ticagrelor group and the clopidogrel group. Previous studies have compared the efficacy and safety of ticagrelor vs. clopidogrel in patients with ACS, AMI, STEMI, NSTEMI, and NSTE-ACS [10][11][12][13][14] . However, there is currently no study comparing the efficacy and safety of ticagrelor vs. clopidogrel in patients with SCAD undergoing PCI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No significant differences were observed in the incidence of major bleeding between the ticagrelor group and the clopidogrel group. Previous studies have compared the efficacy and safety of ticagrelor vs. clopidogrel in patients with ACS, AMI, STEMI, NSTEMI, and NSTE-ACS [10][11][12][13][14] . However, there is currently no study comparing the efficacy and safety of ticagrelor vs. clopidogrel in patients with SCAD undergoing PCI.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies showed that ticagrelor was associated with an increased risk of bleeding events compared with clopidogrel in patients with AMI 11,[28][29] , NSTEMI 13) , and ACS [30][31][32] . However, the PLATO study and other studies revealed that ticagrelor did not increase the bleeding risk compared with clopidogrel in patients with ACS 33) , NSTE-ACS 14) , and STEMI 12,34) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, clopidogrel is the most frequently used P2Y12 inhibitor in both ACS and CCS, accounting for about 50% to 80% of cases of P2Y12 inhibitor use worldwide [ 13 , 14 , 15 , 16 , 17 ]. However, our data showed that clopidogrel was used only in 24% of patients, while prasugrel was used in 76% of patients in the Japanese ACS registry.…”
Section: Discussionmentioning
confidence: 99%
“…The occlusive effect of these aggregates combines with their inherent instability and tendency to embolic distal circulation. Thus, this aggregation mechanism may enhance cerebral blood vessel symptoms of acute coronary syndrome and intermittent thromboembolism [71]. In addition, this aggregation process can occur independent of soluble agonists, further illustrating the important role of platelet aggregation mechanism driven by hemodynamic changes [11].…”
Section: P2y12 Receptor and Atherosclerosismentioning
confidence: 95%